Probation and parole in California: an experiment in community corrections reform - Kras, Kimberly Raye (The Routledge handbook on global community corrections, 2024)
The correctional system in California, U.S.A. is one of the largest in the world, responsible for nearly 300,000 people on community-based forms of supervision. Probation and parole agencies in California are tasked with promoting a client-centered post-conviction experience aimed at addressing underlying needs through service referrals and monitoring and compliance activities to ensure successful completion of supervision. In this chapter, we will describe the adult community-based supervision system of probation and parole in the state of California, including its history, legislation, organizational structure, and implementation of community corrections reforms in risk/need classification, supervision, treatment, and control of individuals placed in this state's community corrections system. The use of technology and other innovations are also discussed.